Relação entre disfunção temporomandibular e alterações posturais: uma revisão narrativa - Giovanna Paôla da Cunha Nunes Nader (2011)
The relation between temporomandibular joint disorders and postural changes (head and neck) has been widely studied although little has been clarified. The aim of this study was to review the literature in order to verify the existence of a correlation between temporomandibular disorders and postural changes in head and neck. According to the literature reviewed, five of the eighth articles assessed showed the existence of a relation between head and neck posture and temporomandibular disorders. These studies were: Oliveira e Arcanjo (2008), Saito et al. (2009), Miranda et al. (2010), Neto et al. (2010) e Pasinato et al. (2008). On the other hand, three studies, Iunes et al. (2009), Andrade e Teixeira Salmela (2006) e Biasotto - Gonzales et al. (2008), did not verify this significant relationship. In conclusion, more studies are necessary to ensure the relationship between temporomandibular disorders and postural changes in head and neck.